Early treatment outcomes of class II malocclusion with twin-block facial profile and cephalometric changes - Mousumi Goswami Singh; Pallavi Vashisth; Seema Chaudhary; Ashish Sinha (Elsevier, 2012)
ABSTRACT: Esthetic improvement is highly valued by patients seeking orthodontic treatment. Subjects with a class II malocclusion are a good example of patients who seek treatment primarily for esthetic improvement. A young growing child with convex profile due to a small, retropositioned mandible, normal midface and lower tip trap is more suitable for functional appliance treatment. Functional appliances encourage adaptive skeletal growth by maintaining the mandible in a corrected forward position for a sufficient period of time to allow adaptive skeletal changes to occur in response to a functional stimulus. The aim of this article is to describe two cases of class II malocclusion in late mixed dentition period treated with twin-block. The cephalometric and facial profile changes have been discussed